2016
DOI: 10.1111/mmi.13571
|View full text |Cite
|
Sign up to set email alerts
|

Robust Min‐system oscillation in the presence of internal photosynthetic membranes in cyanobacteria

Abstract: The oscillatory Min system of Escherichia coli defines the cell division plane by regulating the site of FtsZ-ring formation and represents one of the best-understood examples of emergent protein self-organization in nature. The oscillatory patterns of the Min-system proteins MinC, MinD and MinE (MinCDE) are strongly dependent on the geometry of membranes they bind. Complex internal membranes within cyanobacteria could disrupt this self-organization by sterically occluding or sequestering MinCDE from the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 94 publications
2
51
0
Order By: Relevance
“…1B). This increase in size is anticipated, as MinC disrupts FtsZ polymerization, thereby delaying the establishment of a divisome and onset of cell septation (16,21,22). Upregulation of mTurq-MinE also increased cell size (Fig.…”
Section: Engineering Cell Morphology Of Cyanobacteriamentioning
confidence: 94%
See 4 more Smart Citations
“…1B). This increase in size is anticipated, as MinC disrupts FtsZ polymerization, thereby delaying the establishment of a divisome and onset of cell septation (16,21,22). Upregulation of mTurq-MinE also increased cell size (Fig.…”
Section: Engineering Cell Morphology Of Cyanobacteriamentioning
confidence: 94%
“…MinC, MinD, and MinE were N-terminally tagged, while Cdv3 was C-terminally tagged. We have previously demonstrated that tagged MinC or Cdv3 can fully replace the endogenous copy without causing phenotypes associated with ΔminC or Δcdv3 backgrounds (16). Furthermore, both mTurq-MinD and mTurq-MinC retained the capacity to oscillate within the cell.…”
Section: Engineering Cell Morphology Of Cyanobacteriamentioning
confidence: 99%
See 3 more Smart Citations